Fabrication, characterization and functional attributes of zein-egg white derived peptides (EWDP)-chitosan ternary nanoparticles for encapsulation of curcumin: Role of EWDP. (15th March 2022) - Liu, Jingbo; Li, Yajuan; Zhang, Hui; Liu, Shitong; Yang, Meng; Cui, Meiyan; Zhang, Ting; Yu, Yiding; Xiao, Hang; Du, Zhiyang
Highlights: Zein-EWDP-chitosan ternary nanoparticles were fabricated to deliver curcumin. EWDP exhibited properties as both a nutraceutical and affinity agent. The addition of EWDP showed better encapsulation efficiency to curcumin. EWDP and curcumin exerted a synergistic effect in the ternary nanoparticles. EWDP combined with CS enhanced the various stability of curcumin. Abstract: The food-derived peptides hydrolyzed from native food protein matrix exhibited various bioactivities and multimeric structures, which make them the promising well-defined nanoplatforms candidates to co-deliver themselves with other bioactive compounds. In this study, zein-egg white derived peptides-chitosan (Z-EWDP-CS) ternary nanoparticles (NPs) were successfully fabricated by the spontaneous assembly to enhance the stability and bioactivity of curcumin (Cur). The novel ternary NPs exhibited a typical nano-spherical structure (138.63 nm, 40.50 mV), and adorable encapsulation efficiency (EE, 93.87%) for Cur. FTIR, XRD and DSC results verified that Cur changed from a crystalline state to an amorphous state, and was successfully entrapped in the cavity of Z-EWDP-CS NPs. Furthermore, the thermal stability, photochemical stability, salt stability, and antioxidant activity were considerably improved in the NPs after the addition of EWDP. Our results demonstrate that the food-derived peptides could be an ideal affinity agent for the co-delivery of themselves with hydrophobic nutraceuticals.